2020
DOI: 10.2337/db20-0156
|View full text |Cite
|
Sign up to set email alerts
|

Active Cigarette Smoking Is Associated With an Exacerbation of Genetic Susceptibility to Diabetes

Abstract: The heritability levels of two traits for diabetes diagnosis, serum fasting glucose (FG) and glycated hemoglobin (HbA 1c ), were estimated to be 51-62%. Studies have shown that cigarette smoking is a modifiable risk factor for diabetes. It is important to uncover whether smoking may modify the genetic risk of diabetes. This study included unrelated Taiwan Biobank subjects in a discovery cohort (TWB1) of 25,460 subjects and a replication cohort (TWB2) of 58,774 subjects. Genetic risk score (GRS) of each TWB2 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…DNAm occurs predominantly at cytosine‐phosphate‐guanine (CpG) sites (6). Environmental factors such as smoking are associated with changes in methylation levels (7‐10). In contrast with DNA sequences, which remain stable throughout the lifetime, DNAm levels are dynamic and they can reflect physiological alterations (11).…”
Section: Introductionmentioning
confidence: 99%
“…DNAm occurs predominantly at cytosine‐phosphate‐guanine (CpG) sites (6). Environmental factors such as smoking are associated with changes in methylation levels (7‐10). In contrast with DNA sequences, which remain stable throughout the lifetime, DNAm levels are dynamic and they can reflect physiological alterations (11).…”
Section: Introductionmentioning
confidence: 99%
“…A recent replication study in Taiwan showed that genetic susceptibility to diabetes might be intensified by active smoking. 21 Most recently, genome-environment-wide interactive studies on T2D also provided evidence for genetic interactions with active smoking. 11 Despite these observations, the probable biologic pathways or regulatory mechanisms to clarify these associations remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The TWB research team obtained ethical approval for the program from the Ethics and Governance Council of Taiwan Biobank and the Institutional Review Board on Biomedical Science Research/IRB-BM in Academia Sinica. 21 Data from 52 participants were incomplete and hence were excluded. In the final analysis, data were from 22,039 participants (11,049 women and 10,990 men).…”
Section: Study Participants and Identification Of T2dmentioning
confidence: 99%
“…The Institutional Review Board on Biomedical Science Research in Academia Sinica and the Governance Council of Taiwan Biobank had approved the TWB project. 19 Biobank participants had provided written informed consent before enrollment. This study was approved by the Institutional Review Board of Chung Shan Medical University (CS1-20009).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the genotyping procedures have been described elsewhere. 19 In this study, we chose the LRRK2 rs10506151 variant based on its previous associations with neurodegenerative diseases. This variant passed the quality control test: call rate (>95%), Hardy-Weinberg equilibrium test (p>1.0 × 10 −3 ), and minor allele frequency (>0.05).…”
Section: Methodsmentioning
confidence: 99%